Harvesting of wild climbers, food security and ecological implications in Bwindi Impenetrable National Park, S.W uganda - Bitariho, Robert; Akampurira, Emmanuel (Bwindi Mgahinga Conservation Trust, 2019)
Humans have harvested wild climbers from forests for subsistence and commercial use for thousands of years. In the early four decades, wild climbers were considered a “nuisance” by foresters claiming they suppressed timber tree production and therefore cleared expanses of forests free of the wild climbers. This trend was nevertheless discarded later on, after the realizations that the wild climbers played crucial roles in the rural economies of most tropical countries. Wild climbers (lianas and vines) have played important roles in the livelihoods of people locally and internationally. The use of wild forest climbers is more evident in the tropics, where they are used by rural farmers in food and cash crop production processes. The importance of wild climbers in rural economies for suste¬nance of food security in homesteads cannot, therefore, be overemphasized. In Bwindi Impenetrable National Park (BINP), the exploitation and use of wild climbers by local communities has been ongoing long before BINP was designated a national park. Currently local communities harvest wild climbers within a framework of Uganda Wildlife Authority’s (UWA) Multiple Use Program (MUP). It is against this back¬ground that this study was designed, to assess the ecological and food security implications of the exploitation of the wild climbers in BINP. The study was carried out in parishes surrounding the park (Bushura, Rutungunda, Eastern Ward and Southern Ward) where climber harvesting by the local people was legalized in 1994 by UWA. Fifty-six resource users were interviewed of which 67% were males and 33% were females. Household surveys involving 120 respondents (58% were males and 42% were females) were conducted. Forest surveys and inventories were carried out to assess the abundance and distribution of the harvested wild climbers in the BINP forest. The forest survey method used followed an adaptive management approach that focused on the category of the wild climbers plants being harvested. The wild climbers sustainable harvest levels were based on size, class, distribution and regeneration characteristics. This data was then compared with the household survey data on food security and use of alterna¬tives in the study parishes. Eight different types of wild climber products were made by resources users around BINP and these were; fishing baskets, beehives, granaries, ordinary baskets, mats, small baskets (ebibo), tea baskets and winnowing trays. The most common types of food security related products found in homesteads were; small baskets (ebibo), followed by mats, then ordinary baskets, winnowing trays and tea baskets. Each household had an average of 2.3 small baskets, 2 mats, 1.6 ordinary baskets and 1.5 winnowing trays all made from wild climbers. The least common type of household wild climber products were the granaries and others like grinding trays. The most commonly used wild climbers in the study area for making food security products were; Smilax anceps (18%) followed by Monathotaxis littoralis (15%), Dracaena laxissima (8%) and Marantochloa manni (6%). The most used alternative products in the households were synthetic nylon bags (18%) and synthetic nylon mats (18%). The most used alternatives to make products were plastics/nylon (26%), followed by eucalyptus trees (18%), metals & steel (13%) and banana fibres (5%). Granaries made from Pristimera gracilifolia, small baskets made from Maranto¬chloa mannii and tea baskets made from Loeseneriella apocynoides were the most expensive wild climber products that were each sold at UGX 33,000, 25,000 and 20,000 respectively. The cheapest products were the winnow¬ing trays and mats made from Triumfetta brachyceras sold at UGX 3,000 and 2,500 respectively. According to the respondents, the high pricing of the wild climber products such as winnowing trays and baskets was their biggest limitation to using wild climbers. This was attributed to the increasing difficulty in obtaining the wild climbers used in making those products within the area. The size, class and distributions of most of the useful wild climbers harvested showed a healthy regenerating plant population that is expected of populations that recruit successfully and continuously over time. This is an indicator of a stable size structure of a self-replacing plant population and therefore indicates a sustainably harvested plant population in BINP. However, a few other plants such as Loeseneriella apocynoides, Toddalia assiatica and Monan¬thotaxis littoralis showed a size, class and distribution that has been heavily harvested by the local people. These three plants are widely used in making of winnowing trays, baskets and granaries that are important for food security in households. In conclusion, wild climbers provide important raw materials used in the making of products for handling, process¬ing and storage of food crops and therefore important in safeguarding food security in rural poor households around BINP. Despite this, the wild climbers are continually being replaced by alternatives such as synthetic nylon sacks and plastic basins, among others, because of the unavailability, none free access and expensiveness of the wild climbers. Thus, more and more people are continually and gradually shifting to use of alternative synthetics for food storage purposes. It goes without saying; that the use of synthetics such as nylon sacks and plastic basins is detrimental to the environment and the soils around BINP. The study recommends increased access to the wild climbers (that are not heavily harvested) by the local people through increased and allowable off-take quotas by park officials. Furthermore, more efforts needs to be put towards planting of these widely used wild climbers in local community lands for future use and conservation of genetic materials. More efforts should be put in on-farm cultivation of the important wild climbers that are suf¬ficiently valuable to local communities. The Institute of Tropical Forest Conservation (ITFC) has an ethnobotanical garden at Ruhija that breeds indigenous tree seedlings and can be facilitated to enhance the production of the wild climbers useful to the local communities. Although the use of synthetic materials such as plastics and nylons is slowly but gradually replacing the wild climbers, we discourage their use since the plastics and other synthetics materials have been proven to be detrimental to the environment and soils alike.
Keywords: Harvesting; Wild climbers; Food security; Ecological implications; National Park; Uganda